2016
DOI: 10.1016/j.jcv.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus detection in fine needle aspiration cytology of lymph node metastasis of head and neck squamous cell cancer

Abstract: In this study, testing on HPV in FNAC of cervical lymph node metastases of SCC is validated. It provides a valuable alternative for testing of HPV on histological material from patients with oropharyngeal squamous cell carcinoma or cancer of an unknown primary tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…HPV‐DNA status in FNA was analysed using a highly sensitive genotyping assay that displays an excellent performance on FFPE tissues. Only one previous study used the same primer set of the INNO‐LiPA HPV Genotyping Test to assess HPV‐DNA in FNA . We found no invalid results, and we observed HPV‐positivity in more than 60.0% of the tested specimens.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…HPV‐DNA status in FNA was analysed using a highly sensitive genotyping assay that displays an excellent performance on FFPE tissues. Only one previous study used the same primer set of the INNO‐LiPA HPV Genotyping Test to assess HPV‐DNA in FNA . We found no invalid results, and we observed HPV‐positivity in more than 60.0% of the tested specimens.…”
Section: Discussionmentioning
confidence: 47%
“…Other studies that used a PCR‐based method found a false‐negative result in 4‐5% of the FNA specimens . However, differently from our study, in which liquid‐based FNA samples were employed, these last studies used cell material scraped from the slide.…”
Section: Discussionmentioning
confidence: 67%
“…However, specific data on HPV are lacking in this cohort because most patients were diagnosed by fine needle aspiration (FNA) only and that p16 testing was not widely performed until after 2010. Despite a recent report on the technical feasibility of performing HPV on FNA specimens [23], this was not routine at the time and not done on our specimens.…”
Section: Plos Onementioning
confidence: 95%
“…A meta-analysis of retrospective studies by Ragin et al [6] indicated that patients with HPV-positive OPSCC exhibited markedly reduced risk of mortality compared to patients affected by HPV-negative OPSCC. Fine needle aspiration cytology (FNAC) with ultrasonography, computed tomography (CT), and MRI are the techniques generally used for the local staging of OPSCC, while positron emission tomography (PET)-CT is useful in locally advanced stages and for carcinomas of unknown primary origin [7][8][9][10][11]. Several studies [11][12][13][14] have reported differences in imaging features of OPSCC by HPV status.…”
Section: Introductionmentioning
confidence: 99%